PENTINGNYA PERTUMBUHAN KARAKTER DI DALAM KEHIDUPAN ORANG MUDA MENURUT TULISAN ELLEN WHITE - Kasingku, Juwinner; Robert Siby (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The changes in time and advancements in technology have had a negative effect on the morals of teenagers, as shown by the increase in cases of violence, bad behavior, and weak self-control. The lack of character education is a major reason for the moral crisis among young people. This study aims to look into the importance of character development according to the writings of Ellen G. White and how it can be applied in daily life. The method used is a review of literature, especially the works of Ellen White, with a qualitative approach to understand the importance of Christian character. The results show that true character is built through a close relationship with God through prayer, studying the Bible, self-discipline, good habits, and following the example of Christ. Ellen White points out that character is not formed quickly, but through personal effort and God's grace. Character development also prepares us for eternal life and helps protect us in facing the challenges of the end times. In conclusion, character development according to Ellen White is very important in addressing the moral crisis among teenagers today. Education based on God's principles in His Word needs to be applied consistently so that young people can live with integrity, reflect God's character, and have a positive impact on society.